pH measurement for watering plants system using internet of things (IoT) - Oktafiandri, Viko; Yuwanda, Yuda; Arifiansyah, Rafli; Tupal, Pande (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The development of Internet of Things or IoT technology is currently widely used to connect objects such as smartphones or actuators to the internet so that we can control it and enable forms of communication both between objects and with humans. In this study, water quality control was carried out where water that has good quality is if the water is not excessively polluted by harmful chemicals or minerals. One indicator that water is polluted is the pH (acidity) of water. Where the neutral pH of water has a pH value that ranges from 6.5 to 7.5. Neutral pH control for watering this plant uses a pH sensor as a water acid detector which will provide an input signal to the microcontroller. The system optimizes water usage by ensuring irrigation only occurs when both pH and soil moisture levels are within acceptable ranges. Therefore, in this study a monitoring device was developed using Blynk where the Arduino Uno microcontroller device will be integrated with the ESP8266 Wi-Fi module which is connected to the Blynk application that is installed on the smartphone device. Combines advanced IoT technologies with agricultural practices, revolutionizing traditional methods of water pH monitoring and irrigation for the future.